Analisis Dokumentasi Kunjungan Masa Nifas Berdasarkan Data EMR di Puskesmas Nalumsari I - Evita Aurilia Nardina; Ratih Kumala Dewi; Endah Wijayanti (Pusat Riset dan Inovasi Nasional, 2025)
Postpartum visit documentation is a vital component of midwifery care, serving not only as a clinical record but also as an indicator of service quality. The use of Electronic Medical Records (EMR) in primary healthcare settings is expected to improve the accuracy and completeness of postpartum care documentation. This study aimed to analyze the completeness of postpartum visit documentation based on EMR data at Nalumsari I Public Health Center, Jepara Regency. A descriptive quantitative design with a retrospective approach was used to assess 120 postpartum medical records from 2023. The findings showed that the most consistently documented components were blood pressure (98.3%) and uterine involution (95.8%), while psychological status and health education were less frequently recorded (65% and 58.3%, respectively). The Chi-Square test revealed a significant relationship between the number of postpartum visits and the completeness of documentation (p = 0.001). These results indicate that more frequent visits are associated with more complete and higher-quality documentation. This study implies the need to strengthen health workers' capacity in EMR-based documentation, especially in recording non-clinical aspects such as emotional support and postpartum health education.